Design and Building of Android Based Room Facility Lending Application - Dicky Giancini (International Journal of Computer, Network Security and Information System, 2020)
Android is a platform that is currently used by many users, so that almost every application created uses the Android platform because it is easy to use and also effective. The Faculty of Computer Science UPN